Impact of Hospital Wastewater on the Occurrence and Diversity of Beta-Lactamase Genes During Wastewater Treatment with an Emphasis on Carbapenemase Genes: A Metagenomic Approach - Hubeny, Jakub; Ciesielski, Sławomir; Harnisz, Monika; Korzeniewska, Ewa; Dulski, Tomasz; Jałowiecki, Łukasz; Płaza, Grażyna (Frontiers in Environmental Science, 2021)
The diversity of beta-lactam antibiotic resistance genes, with particular emphasis on carbapenemase genes, during the treatment process at two wastewater treatment plants (WWTPs) with different levels of hospital wastewater inflow was investigated using high-throughput sequencing. An additional aspect of the study was to determine the taxonomic diversity of microorganisms in the studied samples. The obtained results suggest that bacteria of the Fusobacteriaceae family, not associated to date with this phenomenon, may be involved in the spread of antibiotic resistance in the environment. In samples from both wastewater treatment plants, the dominant beta-lactamase genes included blaOXA, blaGES, blaBEL, blaCfxA, and blaTEM. It is worth noting that the blaKPC and blaNDM genes were only found in untreated municipal wastewater with a higher hospital wastewater content. Moreover, an increase in the abundance of the blaIMP gene after the biological treatment stage in the studied treatment plants was found. In wastewater characterized by a higher proportion of hospital wastewater, 94 correlations were observed, while in wastewater with its lower proportion, 41 correlations were noted. Considering the above, the current research indicates that the inflow of hospital wastewater contributes to the spread of antibiotic resistance in the aquatic environment.